The response of mobile intertidal invertebrates to subsistence harvesting in Northern KwaZulu-Natal - Morgan, Derek (Department of Biological Sciences, 2023)
The Response of mobile intertidal invertebrates to subsistence harvesting in Northern KwaZulu Natal was investigated. Spatial scale comparisons were made between as well as within harvested and non-harvested locations. The difference in three population variables was investigated: i) abundance of species groups. ii) size structure of each organism and iii) community structure of mobile organisms. Abundance analysis revealed no significant difference between harvested and no harvested regimes for most species' groups, excepting Snails and Chitons. Snails were more abundant und chitons less abundant at harvested sites. A significant difference.... between locations was however noted, for all species groups, suggesting that variation in abundance within is more prominent than between harvesting regimes. Size stmcturc analysis revealed significantly larger sizes for most spec1cs at non harvested locations, with only Morula gm1111/u111 and Scutellastm exusw showing u significantly larger size structure at non-harvested locations. Community structure analysis revealed no clear distinction between or wi1hin harvested locations. A decrease in size structure with no co1Tespondi11g density effect may be a function of the preference of harvesters for larger individuals, thereby favouringjuveaile populations. The possibility also exists that density effects have been masked due to the use of size instead of biomass data. Converting to size data to biomass, using wet mass versus size regressions, may be a more appropriate analysis method. The observed differences in community structure between as well ru; within loi:-ations indicates that the intertidal communities are inl1erintly hcterogenous in this area. ln order 10 determine the irnpacr of exploitation. spatial scale comparisons between harvesting regimes thus ideall y need to be conducted to each location. [n this study there was also a lack of representative control sites, us unharvested locatio11s are impacted by fisherman and tourists. A possible strategy would be to demarcate "110-go" areas in harvested and non-harvested areas, to serve as both controls and provide broodi11g stocks for adjacent ledges. It is however recommended that more research emphasis be placed on U1e user in evaluating the effects ofhurmtn tmpact on intertidal resource.